2021
DOI: 10.1177/14613557211064055
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life, emotional and physical well-being of police personnel in India

Abstract: The job profile of police officers places exceptional demands on them leading to risks to life, personal discomfort and stress. This article aims to examine how the physical and emotional well-being of police personnel is affected by their perceived quality of work life (QWL). The study looked at the questionnaire responses of 234 police personnel. Emotional well-being is measured as the absence of depression, emotional hyperactivity, difficulty relaxing, irritability and anxiety, whereas physical well-being i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The last decades have seen a growing number of studies exploring employee well-being in different organizational contexts (Danna and Griffin, 1999;Diener, 2009;Warhurst and Knox, 2022;Yadav et al, 2021;Rastogi et al, 2018, Grote andGuest, 2017;Ryan and Deci, 2001;Ryff, 1989). Employee well-being demonstrated various positive organizational outcomes, for instance, organizational performance, job satisfaction, work engagement and avoidance of burnout (Ilies et al, 2015).…”
Section: Dimensions and Influences Of Employee Well-beingmentioning
confidence: 99%
“…The last decades have seen a growing number of studies exploring employee well-being in different organizational contexts (Danna and Griffin, 1999;Diener, 2009;Warhurst and Knox, 2022;Yadav et al, 2021;Rastogi et al, 2018, Grote andGuest, 2017;Ryan and Deci, 2001;Ryff, 1989). Employee well-being demonstrated various positive organizational outcomes, for instance, organizational performance, job satisfaction, work engagement and avoidance of burnout (Ilies et al, 2015).…”
Section: Dimensions and Influences Of Employee Well-beingmentioning
confidence: 99%
“…It is on this basis that Storman et al (2022) maintained that QWL is an important approach to saving human and environmental values which have been neglected due to growing demands of economic growth and productivity. It is no longer a new issue in the organisation as most research conducted by various scholars has demonstrated that QWL is the most vital priority that should be considered by organisations if improvement in organisational performance will be achieved (Yadav and Khanna, 2022;Tarigan et al, 2021). QWL refers to the favourableness and unpleasant nature of the job environment for the entire workforce.…”
Section: Introductionmentioning
confidence: 99%